Climate variability drives anchovies and sardines into the North and Baltic Seas - Alheit, Jürgen; Pohlmann, Thomas; Casini, Michele; Greve, Wulf; Hinrichs, Rosemarie; Mathis, Moritz; O'Driscoll, Kieran; Vorberg, Ralf; Wagner, Carola (Progress in Oceanography, 2012)
European anchovy (Engraulis encrasicolus) and sardine (Sardina pilchardus) are southern, warm water species that prefer temperatures warmer than those found in boreal waters. After about 40 years of absence, they were again observed in the 1990s in increasing quantities in the North Sea and the Baltic Sea. Whereas global warming probably played a role in these northward migrations, the North Atlantic Oscillation (NAO), the Atlantic Multidecadal Oscillation (AMO) and the contraction of the subpolar gyre were important influences. Sardine re-invaded the North Sea around 1990, probably mainly as a response to warmer temperatures associated with the strengthening of the NAO in the late 1980s. However, increasing numbers of anchovy eggs, larvae, juveniles and adults have been recorded only since the mid-1990s, when, particularly, summer temperatures started to increase. This is probably a result of the complex dynamics of ocean–atmosphere coupling involving changes in North Atlantic current structures, such as the contraction of the subpolar gyre, and dynamics of AMO. Apparently, climate variability drives anchovies and sardines into the North and Baltic Seas. Here, we elucidate the climatic background of the return of anchovies and sardines to the northern European shelf seas and the changes in the North Sea fish community in the mid-1990s in response to climate variability